Environmental conditions, air pollutants, and airway cells in runners: A longitudinal field study - Chimenti, L.; Morici, G.; Paternò, A.; Bonanno, A.; Vultaggio, M.; Bellia, V.; Bonsignore, M. R. (Journal of Sports Sciences, 2009)
Runners have increased numbers of neutrophils in the airways at rest and after exercise compared with sedentary individuals. The aim of this study was to determine whether Mediterranean seasonal changes in temperature, humidity or airborne pollutants affect the airway cells of runners training outdoors in an urban environment. In nine male amateur runners, cell composition, apoptosis, and inflammatory mediators were measured in induced sputum collected at rest (baseline) and the morning after races held in the fall (21 km), winter (12 km), and summer (10 km). Concentrations of air pollutants were below the alert threshold at all times. Neutrophil differential counts tended to increase after all races (P = 0.055). Apoptosis of neutrophils increased with ozone (P < 0.005) and particulate matter <10 µm (PM10) (P < 0.05) exposure. Bronchial epithelial cell counts were low at all times and weakly correlated with ozone and PM10 concentrations. Apoptotic bronchial epithelial cells increased after all races (P < 0.05). Inflammatory mediators in induced sputum were low at baseline and after the races, and correlated with neutrophil differential counts only at rest. In conclusion, apoptosis of airway cells in runners appears to be affected by both exercise and environmental conditions. Apoptosis of neutrophils increased with exposure to environmental pollutants while apoptosis of bronchial epithelial cells increased after intense exercise. Since no relationship was observed between neutrophil counts and inflammatory mediators 20 h after races, airways inflammation at this time point appears blunted in healthy runners and little affected by exposure to mild seasonal changes and airborne pollutants.